Dinamika Tanggung Jawab Pendidikan Karakter Anak dalam Sistem Kekerabatan Minangkabau - Yuslistia Opeska; Ahmad Rifki; Sudawan Supriadi; Aminah Ramalia (MAN 4 Kota Pekanbaru, 2025)
Problems related to children's character are still a problem related to the frequent occurrence of deviations in their behavior. In Minangkabau society, there is a slightly different view of the role holder in developing children's character, namely involving the role of Mamak or the mother's brother to share responsibility for the character that grows in children (nephews). The study aims to describe the responsibility for children's character education in the Minangkabau kinship system, and to analyze the dynamics of the responsibility for children's character education in the Minangkabau kinship system and the causes. This study uses a literature review, which is part of a qualitative descriptive method using relevant reading sources. The results of the analysis show that there has been a shift in the responsibility for children's character education from Mamak to parents as a whole, caused by the Mamak's work which results in their own busyness, then the Mamak's busyness with their respective families.